Evaluation of the Shear Strength of RC Beams Strengthened by Basalt Fiber Sheets - Kashash, Muhaned Dawood; Khalid, Nibras Nizar (Engineering, Technology & Applied Science Research, 2025)
The present study experimentally investigates the use of Basalt Fiber-Reinforced Polymer (BFRP) composites for the shear strengthening of High-Strength Reinforced Concrete (HSRC) beams. The objectives of this work are to investigate the contribution of BFRP in enhancing the shear capacity and ductility of HSRC beams across different shear span-to-effective depth (a/d) ratios and to assess the effect of the number of BFRP sheet layers on shear strength improvement. The experiment involved U-wrapped 90° BFRP strips applied to HSRC beams under shear. Two groups of a/d ratios were used, namely 2.8 and 2.4. A total of eight HSRC beams with and without shear reinforcement were tested under four-point loading. The results indicate that beams with a lower a/d ratio (2.4) exhibited higher ultimate load capacities and improved shear strength compared to those with a higher a/d ratio (2.8). Specifically, for a/d 2.8, the ultimate load capacity increased by 89% with two layers of U-wrapped 90° BFRP strips, and for a/d 2.4, it increased by 49% with the same strengthening compared to the control beams. The application of BFRP U-strips significantly enhanced structural performance, increasing ultimate load capacity and reducing deflections, particularly with multiple layers.